Conservation Agriculture in South Asia - CGIAR Research Program on Wheat (2019)
(a) A meta-analysis of conservation agriculture was conducted with the help of a consultant (b) Data from different regions were compiled and did analysis of the impact of conservation agriculture in India (c) Developed a paper on impact of Happy Seeder in Punjab with A Keil.